(untitled) (Revista de Artes Marciales Asiáticas, 2019)
Capoeira is a simulated duel supported by the rhythmic of instrumentalists, with traditional musical instruments; evolving a constant synchrony with the other capoeirista. Nowadays, capoeira is passed on by traditional processes, according to the past experience and personal interpretations of the Mestre de capoeira (capoeira master/coach). The purpose of this pilot study was to present a preliminary evaluation of a program for learning the basic techniques, for capoeira teaching agents, respecting the cultural and historical values of capoeira’ identity; applied to 15 first-grade school children (Mage = 8.0 ± 1.2 years old), belonging to a non-governmental organization, with integrative social roles, and to a national sports club, all capoeira beginners; throughout 30 sessions (90 minutes each), over three months. Results revealed that a significant improvement occurred in the quality of execution of all the twelve selected capoeira techniques, with no significant differences between genders and institutional origin, sustaining the potential cultural and social affordances of capoeira. The practice in dupla (dyad), in the fundamental ginga ability, provided synchronization among children, from the first moment, in tune with one of the specificities of this body culture movements, with a proper rhythmic structure (reinforced by music), which are performed in pairs. This program should be tested in an enlarged sample, and in other learning contexts (e.g., schools, clubs), to test its applicability.